An efficient key validation mechanism with VANET in real-time cloud monitoring metrics to enhance cloud storage and security. (March 2023) - Lakshmi Narayanan, K.; Naresh, R.
Abstract: A vehicle-specific network (VANET) in automotive networks is formed along the road unit. There are many challenges in quality management to avoid expensive RSUs and improve the quality management of VANET systems. Our proposed work proposes a new algorithmic programme for organizing the cluster structure and choosing cluster headers (CHs) compatible with VANET. Weighted Cluster Protocol (AWCP) teams nodes at random, so it reaches the best channel by optimizing network parameters. The proposed work with analysis of the AWCP EE-WOA model is an automotive network with selected speed and placement. VANET provides a list of vehicles that failed to interact in the preceding period. System administrators should routinely update the generated keys of all the systems' vehicles, and the system administrator should suspend or revoke the power of scenarios. This validation occurs in the cloud whenever the vehicle generates the best algorithm for identifying keys. The results show that the projected AWCP EE-WOA model outperforms the Weighted Cluster Protocol and AWCP Whale algorithmic program protocols in terms of improved encapsulation potency and movability with a maximum cluster efficiency of 96.84.